Late Treatment and Recurrence of Kawasaki Disease in a Moroccan Infant - R. Elqadiry; O. Louachama; N. Rada; G. Draiss; M. Bouskraoui (Case Reports in Pediatrics)
Introduction. While the diagnosis of typical form of Kawasaki disease (KD) is obvious, this multifaceted disease continues to surprise us. We report the case of a recurrent Kawasaki disease in an infant. Case. At the age of 13 months, the infant was diagnosed with complete Kawasaki disease; he presented with prolonged fever, bilateral conjunctivitis, enanthem, exanthema, edema of the lower limb, peeling, and biological inflammatory syndrome. He was treated with intravenous immunoglobulin (IVIG) associated with a high dose of aspirin and then an antiplatelet dose with a good clinical-biological evolution. The echocardiography was normal. Seven months later, the patient was again admitted, in a similar picture: a prolonged fever evolving for 7 days, bilateral conjunctivitis, enanthem, cervical adenopathy of 1.5 cm/1 cm, scarlatiniform erythema, pruriginous of the trunk and limb, and peeling of the toes, with indurated edema of the hands and feet. The rest of the examination was normal except the irritability. The diagnosis of recurrent KD was made according the five criteria of the American Heart Association. The echocardiography was normal again. The infant received IVIG with good outcome. Conclusion. Despite its rarity, the possibility of recurrence of KD should be known by clinicians, so as not to delay the specific management of vasculitis whose stakes in terms of prevention of coronary artery lesions are well known. Our case confirms the possibility of this recurrence.